1997
DOI: 10.1038/sj.ejcn.1600374
|View full text |Cite
|
Sign up to set email alerts
|

Control of bias in dietary trial to prevent coronary recurrences: The Lyon diet heart study

Abstract: Background and Objectives: A major limitation of dietary trials is that double blind design is not feasible. These trials are therefore prone to biases. The Lyon diet heart study is a single-blind secondary prevention trial to test the hypothesis that a Mediterranean-type of diet may prevent recurrences after a ®rst myocardial infarction. A surprising 73% reduction of the risk of new major cardiac events was observed in the experimental group. For this reason, it is important to describe the methods used in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 14 publications
3
32
0
1
Order By: Relevance
“…A modest intake of oily ®sh (or ®sh oil capsules) resulted in a 29% reduction in total mortality during the ®rst 2 y after a myocardial infarction (without any change in total plasma cholesterol concentration) (Burr et al, 1989), while no bene®t was observed from conventional high ®bre and low saturated fat diets. The Mediterranean diet, high in antioxidants, vitamins, oleic acid and n-3 fatty acids, resulted in a 73% reduction in major cardiac events in patients recovering from a myocardial infarction (De Lorgeril et al, 1997). In practice it is likely that advice to adopt this type of diet might be more acceptable than the promotion of low-fat and low-cholesterol diets (Conway, 1998).…”
Section: Coronary Heart-diseasementioning
confidence: 99%
“…A modest intake of oily ®sh (or ®sh oil capsules) resulted in a 29% reduction in total mortality during the ®rst 2 y after a myocardial infarction (without any change in total plasma cholesterol concentration) (Burr et al, 1989), while no bene®t was observed from conventional high ®bre and low saturated fat diets. The Mediterranean diet, high in antioxidants, vitamins, oleic acid and n-3 fatty acids, resulted in a 73% reduction in major cardiac events in patients recovering from a myocardial infarction (De Lorgeril et al, 1997). In practice it is likely that advice to adopt this type of diet might be more acceptable than the promotion of low-fat and low-cholesterol diets (Conway, 1998).…”
Section: Coronary Heart-diseasementioning
confidence: 99%
“…7,8 In the absence of major bias 9 and in view of the good compliance with the experimental diet and the lack of between-group contamination, [7][8][9] the Lyon trial may offer the opportunity to examine the effect of this dietary pattern on overall survival and newly diagnosed cancer rate, although sample size and duration of follow-up were not calculated specifically for this purpose. Given the number of cancers observed in a similar middle-aged CHD population 10 and the Lyon study sample size, the expected number of cancers in this study was calculated to be approximately 40 during a follow-up of 4 years.…”
Section: Arch Internmentioning
confidence: 99%
“…Patients in the experimental group and their families were seen by the dietitian at the randomization visit, 2 months later, and then once a year. The specific techniques used to instruct these patients have been previously described, 9 and compliance with the dietary intervention was checked by a dietary survey (including a 24-hour recallandafoodfrequencyquestionnaireateachvisit)andanalyses of plasma fatty acids. 21 Patients in the control group were expected to follow the dietary advice given by their attending physicians (not involved in the study) and close to the step 1 diet of the American Heart Association (characterized as 30% of total energy as fats, 10% saturated, 10% monounsaturated, and 10% polyunsaturated, and cholesterol intake lower than 300 mg/d).…”
Section: Trial Designmentioning
confidence: 99%
“…Polyphenol-rich foods, such as fruit, vegetables, wine, olive oil, and cocoa, are able to reduce cardiovascular risk and prevent cardiovascular events and death (3)(4)(5)115). Among them, cocoa beans have always been of particular interest, as they are one of the richest polyphenol sources.…”
Section: Resultsmentioning
confidence: 99%
“…A nutraceutical approach has been proposed to counteract the increasing burden of CVD. The consumption of polyphenol-rich foods has been related to a lower risk of cardiovascular events (cardiovascular mortality, myocardial infarction, and stroke) both in the general population and in patients with cardiovascular risk factors in several interventional and epidemiological trials (2)(3)(4)(5). Polyphenols are believed to be largely responsible for this protective role.…”
mentioning
confidence: 99%